Analisis Peran Profitabilitas dalam Hubungan Determinan Kebijakan Dividen - Firza, Syafira Ulya; Agustina, Agustina (Penerbit Goodwood, 2025)
Purpose: This study analyzes the effect of firm size and liquidity on dividend policy, with profitability as a mediating variable. Methodology: This study used a quantitative approach with secondary data. The population in this study consists of 710 non-financial companies listed on the Indonesia Stock Exchange from 2020 to 2022. The sample was selected using purposive sampling, which resulted in 576 observations. Results: The results indicate that firm size and liquidity have a significant effect on dividend policy. Furthermore, the study also shows that firm size and liquidity can indirectly affect dividend policy decisions through firms’ profitability. Conclusions: The study concludes that firm size has a significant positive effect on profitability, and both firm size and profitability significantly influence dividend policy. Liquidity does not have a direct effect on dividend policy, but firm size and liquidity indirectly affect dividend policy through profitability as a mediating variable. Therefore, improving profitability is essential to support sustainable dividend policy implementation. Limitations: This study has limitations regarding the observation period, which only covers data up to 2022, and thus does not reflect the current conditions of the industry. Additionally, the low coefficient of determination (1.2% for profitability and 11.7% for dividend policy) indicates that other factors influencing dividend policy and profitability were not explored in this study. Contribution: This research provides empirical evidence that can be valuable for investors, corporate managers, and researchers to understand how company size and liquidity influence profitability, which in turn affects dividend policy. The findings can help investors make more informed decisions about companies’ dividend strategies while also offering insights for managers on how financial health and company size may shape their approach to dividend distribution.